2012
DOI: 10.1039/c2md20079a
|View full text |Cite
|
Sign up to set email alerts
|

The use of phosphate bioisosteres in medicinal chemistry and chemical biology

Abstract: Phosphate and pyrophosphate groups play a central role in cellular signalling and consequently are of great interest to both medicinal chemists and chemical biologists. However, the design of molecules that can interfere with phosphate-based processes is recognised as a significant challenge, especially when the resulting compounds must show good cellular penetration and stability. Herein, we have reviewed the full range of phosphate bioisosteres currently reported and provided the context of their deployment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
184
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(187 citation statements)
references
References 133 publications
(254 reference statements)
2
184
0
1
Order By: Relevance
“…Medicinal chemists have found a number of phosphate bioisosteres that are recognized by these pockets, but typically there is a considerable loss of binding affinity. 36 An alternative approach is to create phosphate prodrugs in which the phosphate is unveiled following intracellular metabolism by a suitable enzyme.…”
Section: +mentioning
confidence: 99%
“…Medicinal chemists have found a number of phosphate bioisosteres that are recognized by these pockets, but typically there is a considerable loss of binding affinity. 36 An alternative approach is to create phosphate prodrugs in which the phosphate is unveiled following intracellular metabolism by a suitable enzyme.…”
Section: +mentioning
confidence: 99%
“…Literature precedents have indicated that the sulphonyl bismethylene group has similar steric requirements to the phosphate group. Since these two groups differ in electronic characteristics, it may well be the ability of the phosphate group to bear a negative charge that is responsible for its contribution to the activity of PAF [243].…”
Section: Kitsonmentioning
confidence: 99%
“…Nucleotide analogues featuring methylenebisphosphonate linkage are especially interesting since they represent a versatile platform for the synthesis of enzyme inhibitors and important agents for anticancer and antiviral therapy. [1][2][3][4][5] Progress in the development of these species is closely linked with the development of a bioisostere concept whereby methylenebisphosphonates (H2O3P-CXY-PO3H2) are analogues of endogenous pyrophosphate (H2O3P-O-PO3H2). 6,7 During recent decades numerous fundamental researches were made on design and tactical application of phosphate and pyrophosphate isosteres.…”
Section: Introductionmentioning
confidence: 99%